Model Pengasuhan Anak Yatim dalam Pendidikan Agam Islam: Penelitian - Tazali, Imam; Maksum, Maksum; Ma’ruf, Amar; Ellya Verawati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The process of caring for orphans by applying the teachings of the Qur'an and Hadith, it is necessary to have good care and provide their rights as children who have been abandoned by their parents. Therefore, through education, teaching, care and maintaining their property is what the orphans want and the hope of the orphanage as the manager and administrator of the orphans. The purpose of this study is to provide insight into how the model of caring for orphans in this case uses the literature review method or literature review. Literature review is a research written based on the results of a review of various appropriate library materials. The results of the literature review that the model of caring for orphans in Islamic Religious Education uses a model of moral education, morals and good care for the sake of the future.